PEMBELAJARAN BERBASIS SETS SEBAGAI UPAYA MENINGKATKAN KREATIVITAS DALAM PEMECAHAN MASALAH PENCEMARAN LINGKUNGAN - Sugiarto, Agung; Djukri, Djukri (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2015)
The aim of this study is to reveal the effect of SETS-based teaching as an effort to improve creativity in solving the environmental pollution problem and the effectiveness of teaching based on SETS compare to Problem-Based Learning (PBL). The design of this study was Pretest Posttest Control Group Design. The population was students of SMA N 1 Prambanan, Klaten with the student of class X as a sample. To determine the effect of each study, the data was analyzed using the paired t-test. While to determine the effectiveness of teaching in each class, the data was analyzed using the independent t-test. The result of the study shows that SETS-based teaching and PBL can enhance the creativity of solving problems of environmental pollution and the SETS-based teaching indicated more effective to improve the creativity of the student if compared with the PBL. Key words: SETS, PBL, creativity, environmental